Dilemmas associated with local allergic rhinitis - Krzych-Fałta, Edyta; Namysłowski, Andrzej; Samoliński, Bolesław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Local allergic rhinitis (LAR) in patients with no systemic markers of atopy is a very interesting phenomenon due to the lack of any definitive explanation for the mechanism of this IgE-dependent reaction. Some of the recent attempts to explain this phenomenon consider LAR to be closely associated with an allergic reaction, some suggest that this phenomenon is a spontaneous process in the nasal mucosa. Future attempts to elucidate the complexity of inflammatory reactions will undoubtedly establish a clear differential diagnostics algorithm for rhinitis.